Wysiękowe AMD czy żółtkowata dystrofia dołkowo- -plamkowa dorosłych Besta – opis przypadku - Kubicka-Trząska, Agnieszka; Filemonowicz-Skoczek, Agnieszka; Karska-Basta, Izabella; Romanowska-Dixon, Bożena (Klinika Oczna / Acta Ophthalmologica Polonica, 2008)
Purpose: To report a case of Best vitelliform macular dystrophy referred to the Department of Ophthalmology in Krakow with a diagnosis of exudative age-related macular degeneration (AMD). Materials and methods: 70-years old man was diagnosed in our clinic because of a two years history of slow, progressive visual acuity worsening in both eyes with the presence of metamorphopsia. The basic ophthalmic examination was performed with additional diagnostic methods including: colour vision test (Panel D-15), Amsler grid test, contrast sensitivity test (Pelli-Robson chart), fluorescein angiography (FA), indocyanine green angiography (ICGA), electroretinogram (ERG), electrooculogram (EOG) and optical coherence tomography (OCT). Results: Visual acuity in the right eye was: 0.16 and in the left: 0.25. Amsler grid test revealed the presence of bilateral mild metamorphopsia with the relative central scotoma. Pelli-Robson test showed decreased contrast sensitivity perception in both eyes; PO>LO. On fundoscopy in macula of both eyes the symmetrical round, elevated lesions of 1.5 dd with the meniscus of subretinal creamy-yellow masses were present. The early frames of FA showed the presence of round lesions with distinct borders, unchanged in size and shape throught the examination, hypofluorescent in the lower and hyperfluorescent in the upper half of the lesions. Late frames of FA revealed the irregular hyperfluorescence also in lower aspects of the lesions. ICGA showed: round hypofluorescent lesions with isofluorescence in the upper part of the lesions. ERG – revealed no pathology, EOG – showed decreased light response and depressed Arden ratio in both eyes. OCT demonstrated hiperreflectivity of the retinal pigment epithelium with elevation of retina and deletion of the foveolar depression in both eyes. Conclusions: Based on the results of performed tests the diagnosis of the Best vitelliform macular dystrophy was established. In some cases various pathologies involving the macula may mimic the exudative AMD. The basic ophthalmic examination supported by additional diagnostic methods allow to establish the definitive diagnosis in most cases of macular disorders.